EMOTIONAL INTELLIGENCE, WORK ENVIRONMENT, TRANSFORMATIONAL LEADERSHIP THROUGH JOB SATISFACTION ON PERFORMANCE OF EDUCATION AND CULTURE EMPLOYEES MALUKU PROVINCE - Tehubijuluw Zacharias (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the influence of emotional intelligence, work environment, transformational leadership through job satisfaction on employee performance. The population in this study were all employees at the Maluku Provincial Education and Culture Office totaling 296 people. Sampling in this study was 25% of 296 people, namely 74 people. Analysis using path analysis with the help of SPSS 20.00. The results showed that (1) emotional intelligence, work environment, transformational leadership directly affected job satisfaction and employee performance, (2) job satisfaction mediated the influence of emotional intelligence, work environment, transformational leadership on employee performance.